Vuur, as en water - Tineke Nugteren (Religie & Samenleving)
There are groups that prefer to keep themselves below the radar screen of politics and public opinion. This may be indicative of their preferred acculturation strategy as well as of their inability to come forward with a collectively supported representation. In the Netherlands Hindustanis – a group consisting of around 100,000 people with a background of labour migration from India to Surinam, a Dutch colony at that time – may well be in such a situation. By looking more closely at the various processes of loss, maintenance and proliferation regarding the current state of their death rituals I illustrate how below-radar styles of negotiation may work to their advantage.